Pulmonary fibrosis following household exposure to asbestos dust? - Schneider, Joachim (J Occup Med Toxicol, 2014)
An 81-year-old woman was dying from histologically confirmed pulmonary fibrosis without having had any asbestos exposure in the workplace. The lung dust fibre analysis showed significantly increased “asbestos bodies” (AB) (2,640 AB per gram of wet lung tissue) and asbestos fibre concentrations (8,600,000 amphibole fibres of all lengths and 540,000 amphibole fibres with a length ≥5 μm per gram of dry lung tissue). Asbestos exposure was revealed to have occurred during household contact after 27 years of washing her husband’s industrial clothing that had been contaminated by asbestos at his workplace in an asbestos textile factory. Household asbestos dust exposure as a risk or co-factor in the aetiology of the fatal pulmonary fibrosis is discussed.